A deeply rechargeable zinc anode with pomegranate-inspired nanostructure for high-energy aqueous batteries. Issue 44 (1st November 2018) - Chen, Peng; Wu, Yutong; Zhang, Yamin; Wu, Tzu-Ho; Ma, Yao; Pelkowski, Chloe; Yang, Haochen; Zhang, Yi; Hu, Xianwei; Liu, Nian
Abstract : A deeply rechargeable zinc anode material with nanoscale pomegranate-structured was designed and synthesized for the high energy aqueous batteries. Abstract : Rechargeable, Zn-based aqueous batteries because of their advantages of inflammability, high energy density, and low material cost are an attractive alternative to lithium-ion and lead-acid batteries for transportation and grid-scale applications. Historically, zinc anodes have shown low utilization and rechargeability in alkaline electrolytes due to the problems of ZnO passivation and Zn(OH)4 2− dissolution. Herein, we report a nanoscale, pomegranate-structured Zn anode (Zn-pome) fabricated via a bottom-up microemulsion approach to overcome these problems. In the Zn-pome, primary ZnO nanoparticles (ZnO NPs) assemble into secondary clusters after which they are individually encapsulated by a conductive, microporous carbon framework. The small size of ZnO NPs overcomes the issue of passivation, whereas the secondary structure and ion-sieving carbon shell mitigate the dissolution problem. Inductively coupled plasma (ICP) analysis confirms that Zn dissolution from the Zn-pome anode is effectively suppressed, leading to a considerably prolonged cycle life compared to that of a conventional ZnO anode in an alkaline aqueous electrolyte. The Zn-pome anode even maintains the capacity after long resting. This performance is achieved in harsh yet practical conditions: a limited amount of electrolyte, sealed coin cells, and 100% depth of discharge (DOD). This study represents an important step towards producing aqueous, rechargeable, high-energy batteries. In addition, the design principles reported here can be applied to other battery systems involving passivation or dissolution intermediates.